PROGRAMA AABB – UNIJUÍ – PREFEITURA MUNICIPAL - MARTINI, TALITA; MAI, CIBELE; TABORDA, DOUGLAS D. S.; SANTOS, DINALVA F. D.; PINTO, LÍLIAN F.; BOENO, ELEUSA; CAVINATO, LIDIANE; PELISSON, GLADIS; MARTINS, LUCIANE; SCHEWENGBER, NATÁLIA; RAMOS, NICOLE W.; SILVA, CARINA D.; et al. (Salão do Conhecimento, 2013)
Resumo